Perancangan Sistem Smart Grid Dinamis Berbasis Internet of Things (IoT) untuk Optimasi Distribusi Beban Listrik - Chiesa Virgiawan Pasya; Aan Burhanuddin; Agus Mukhtar (Jurnal Engine: Energi, Manufaktur, dan Material, 2025)
The rapid increase in electricity demand, driven by population growth and industrialization, leads to imbalances in load distribution in conventional power systems. Traditional grids, designed for one-way energy flow, are unable to respond to real-time load fluctuations, resulting in outages and reduced operational efficiency. This research aims to design a dynamic IoT-based smart grid system for optimizing electricity load distribution efficiently. The methodology involves the development of an integrated system architecture with sensors to measure voltage, current, and frequency, along with an IoT-based load management algorithm to automatically regulate energy flow. Testing results show that the PZEM-004t and ACS712 sensors provide highly accurate readings with minimal deviation compared to conventional measurement tools. Additionally, the integration of solar panels (PLTS) in the system showed increased utilization of renewable energy, although PLN still dominated. The findings indicate that an IoT-based smart grid can optimize load distribution and improve energy efficiency by reducing reliance on conventional electricity while supporting the use of renewable energy